KARYA TULIS ILMIAH SISWA DALAM KURIKULUM 2013 DAN KURIKULUM MERDEKA - Dewi Hartati, Rahma; Pratiwi, Brillianing; Yunianika, Ika Tri (Universitas Terbuka, 2024)
When learning Indonesian in high school (SMA), scientific writing is one of the outcomes that students must be able to apply in the form of writing. In fact, scientific writing is difficult material for students. According to the 2013 curriculum, the scientific writing material should enable students to effectively compile and communicate their findings. On the other hand, in the merdeka curriculum, scientific writing serves as a report for each project to enhance the Pancasila students' profile (P5). The purpose of this study is to compare the process of writing scientific papers between the 2013 curriculum and the merdeka curriculum and analyze the resulting learning outcomes. The research conducted revealed the following findings: 1) there were differences in the outcomes of scientific writing learning between the 2013 curriculum and the merdeka curriculum, 2) the scientific writing learning process varied, with the 2013 curriculum only including Indonesian language subjects for scientific writing in class XI, while the merdeka curriculum scientific writing allowed collaboration with other subjects, and 3) the scientific writing guidance system in the 2013 curriculum solely focused on learning Indonesian during class, whereas in the merdeka curriculum, students received special guidance outside of class hours.